New Oxford dictionary for writers and editors. (Oxford University Press, 2014)
The New Oxford Dictionary for Writers and Editors is the essential A to Z guide for everyone who works with words. Drawing on the expertise of the Oxford Dictionaries department, it provides authoritative advice on those words and names which raise questions time after time because of spelling, capitalization, hyphenation, and cultural or historical context. As well as lexical terms, there are many proper names included: from place names and personal names to names of institutions, literary references, and books of the Bible. Entries give full coverage of recommended spellings, variant forms, confusable words, hyphenation, capitalization, foreign and specialist terms, proper names, and abbreviations. It is an essential tool for writers, editors, publishers, journalists, and web editors, and together with New Hart's Rules and the New Oxford Spelling Dictionary forms the complete editorial reference set.